METASYNTHESIS: ANALYSIS AND DESCRIPTION OF MATHEMATICAL REASONING CAPABILITY REVIEWED FROM COGNITIVE STYLE - Akbar Dakha Prabowo; Scolastika Mariani; Arief Agoestanto (HISTOGRAM: Jurnal Pendidikan Matematika, 2024)
Reasoning is " skill basic " mathematics and necessary For a number aim-for understand draft mathematics , for use ideas and procedures mathematical in a way flexible and for reconstructing what is understood . Study This use indicator reasoning mathematical namely (1) submit conjecture , (2) provide explanation with models, facts , properties , and relationships , (3) do manipulation mathematical , and (4) interesting conclusion , compose proof , provide reason to another solution . Study This will discuss style cognitive field independent-field dependent , style cognitive reflective-impulsive , and style cognitive systematic-intuitive . Research purposes This For analyze and describe linkages between every style cognitive with ability reasoning mathematical student . Methods used in research This is meta- synthesis . Meta- synthesis can interpreted as qualitative systematic review method , analyzed articles consisting of 9 from 8 articles national and 1 article international . Research result This state that student with style cognitive systematic , reflective , and field independent capable fulfil indicator reasoning more mathematical. Lots compared to student with style cognitive intuitive , impulsive, and field dependent . Study This expected will help reader For get description about linkages every type style cognitive with ability reasoning mathematical student .